Siksa Alam Barzah Menurut Hadis Nabi Muhammad Saw (Study Naskah Kitab Shahih Muslim) - N Nurhadi (Jurnal Penelitian Medan Agama, 2020)
Death means loss of life or separation of spirit from matter, soul from body or body. Talk about death is not a pleasant thing, in general. In fact, almost all humans want to have a long life span, a long life to be in this world. But death is a partner of life. Then after death someone will be buried and moved to the barzah realm. Many verses that relate to life after death, then how are the traditions relating to this matter? The author's research in the book mausu'ah al-hadis al-Nabawiyah, from the perspective of authentic Muslim hadith. So the researcher found the hadith related to the torment of the grave as many as 18 traditions in the book. Of the 18 hadiths of the Muslim history above, the researchers divided into three parts, namely: 1). Hadith about the torment of the grave, Hadith No. 920, 921, 922; 2). Hadith about protection and prayer to avoid siska burial, Hadith No. 924, 925, 926, 927, 928, 929, 930, 1506, 4814 and 4815, 4878 and 4879 and 4899; 3). Hadith about the prayer of spirits to avoid the torment of the grave, Hadith No. 1600 and 1601.